PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA (LPD) DESA PAKRAMAN POYAN DI TABANAN - I Putu Bagus Aldi Andaresta Pratama; Ni Ketut Sariani; I A Cynthia Saisaria Mandasari (Fakultas Ekonomi Universitas Warmadewa, 2022)
This study aims to examine the effect of individual characteristics and organizational characteristics on employee job satisfaction in LPD Poyan Village. The population in this study were employees at the LPD Pakraman Poyan Village in Tabanan. This study used 35 respondents using saturated sampling with data analysis data using multiple linear regression analysis. The results of the study indicate that individual characteristics have a positive and significant effect on employee job satisfaction. Organizational characteristics have a positive and significant effect on employee job satisfaction. Individual characteristics and organizational characteristics simultaneously have a positive and significant effect on employee job satisfaction.